Locust retinoid X receptors: 9-Cis-retinoic acid in embryos from a primitive insect - Nowickyj, Shaun M. (National Academy of Sciences, 2008)
The retinoid X receptor (RXR) is activated by its often elusive cognate ligand, 9-cis-retinoic acid (9-cis-RA). In flies and moths, molting is mediated by a heterodimer ecdysone receptor consisting of the ecdysone monomer (EcR) and an RXR homolog, ultraspiracle (USP); the latter is believed to have diverged from its RXR origin. In the more primitive insect, Locusta migratoria (Lm), RXR is more similar to human RXRs than to USPs. LmRXR was detected in early embryos when EcR transcripts were absent, suggesting another role apart from ecdysone signaling. Recombinant LmRXRs bound 9-cis-RA and all-trans-RA with high affinity (IC(50) = 61.2–107.7 nM; K(d) = 3 nM), similar to human RXR. To determine whether specific binding had functional significance, the presence of endogenous retinoids was assessed. Embryos were extracted by using modified Bligh and Dyer and solid-phase protocols to avoid the oily precipitate that makes this material unsuitable for assay. These extracts contained retinoids (5.4 nM) as assessed by RA-inducible Cyp26A1-promoter luciferase reporter cell lines. Furthermore, the use of HPLC and MS confirmed the presence of retinoids and identified in any embryo, 9-cis-RA, in addition to all-trans-RA. We estimate that whole embryos contain 3 nM RA, including 9-cis-RA at a concentration of 1.6 nM. These findings strongly argue for a functional role for retinoids in primitive insects and favor a model where signaling through the binding of 9-cis-RA to its RXR is established relatively early in evolution and embryonic development.